Insights into the role of endonuclease V in RNA metabolism in Trypanosoma brucei - Daniel García-Caballero (Nature Portfolio, 2017)
Abstract Inosine may arise in DNA as a result of oxidative deamination of adenine or misincorporation of deoxyinosine triphosphate during replication. On the other hand, the occurrence of inosine in RNA is considered a normal and essential modification induced by specific adenosine deaminases acting on mRNA and tRNA. In prokaryotes, endonuclease V (EndoV) can recognize and cleave inosine-containing DNA. In contrast, mammalian EndoVs preferentially cleave inosine-containing RNA, suggesting a role in RNA metabolism for the eukaryotic members of this protein family. We have performed a biochemical characterization of EndoV from the protozoan parasite Trypanosoma brucei. In vitro, TbEndoV efficiently processes single-stranded RNA oligonucleotides with inosine, including A to I-edited tRNA-like substrates but exhibits weak activity over DNA, except when a ribonucleotide is placed 3′ to the inosine. Immunolocalization studies performed in procyclic forms indicate that TbEndoV is mainly cytosolic yet upon nutritional stress it redistributes and accumulates in stress granules colocalizing with the DEAD-box helicase TbDhh1. RNAi-mediated depletion of TbEndoV results in moderate growth defects in procyclic cells while the two EndoV alleles could be readily knocked out in bloodstream forms. Taken together, these observations suggest an important role of TbEndoV in RNA metabolism in procyclic forms of the parasite.